Czech Republic : Intergovernmental Fiscal Relations in the Transition - do Carmo Oliveira, Joao (Washington, DC: World Bank, 2013)
The study overviews the most relevant, current intergovernmental fiscal issues in the Czech Republic, centered on the options available to prod policy planning. Fragmentation at the lowest tier of government is the most striking feature of the administrative structure. This suggests a strategic direction for further administrative reforms to sustain fiscal decentralization, which includes empowering territorial self-governing units; establishing a multilevel government coordinating body to define autonomous functions on expenditures, and revenues; and by creating financial and legal incentives to facilitate an asymmetric assignment of revenue and expenditure. Specific policy actions should include institutional inter-governmental cooperation and dialogue through a broad based commission to recommend regional expenditures, and the Budget Rules Law should be amended to preempt unfounded mandates to local governments. Revenue autonomy should be boosted by increasing predictability of local budgets, restoring tax-effort incentives, and reviewing the adopted adjustment coefficient for tax-sharing distribution; while a rationalized transfer system should focus on decreasing the number of specific subsidies, and prioritizing programs to stabilize transfers within a medium-term expenditure framework. Institutional framework and prudential rules would ensure fiscally responsible borrowing, and encourage a competitive financial market.